Burden and Hope: A Semiotic Analysis of Emotional Differences on BTS Jin’s Solo Project - Hillary Mayor; Yusnita Febrianti; Kukuh Prayitno Subagyo; Nanang Zubaidi (JoLLA: Journal of Language, Literature, and Arts, 2023)
The semiotic analysis seeks to find the hidden meaning behind a sign. This study investigates the emotional differences in the song lyrics in BTS Jin's solo projects, Abyss and The Astronaut. The meaning and emotional differences obtained through this analysis are denotation, connotation, and myth. This study uses a qualitative method with an interpretative approach using Barthes' (1964) theory of semiology. The result of the study shows that there are two emotional differences conveyed by the two songs in BTS Jin's solo project. The song Abyss tells about Jin's experience when he felt burdened in the process of knowing and learning other personas in him. The Astronaut, on the other hand, a song about how his fans gave him hope and helped him escape the zone where he felt burnout. The emotional differences conveyed by the two songs are Burden in the Song Abyss and Hope in The Astronaut song. Keywords: semiotics; emotional differences; song lyrics; Kim Seok-Jin Burden and Hope: Analisis Semiotika Perbedaan Emosional dalam Proyek Solo Jin BTS Analisis semiotik berupaya menemukan makna tersembunyi di balik suatu tanda. Penelitian ini menyelidiki perbedaan emosional dalam lirik lagu dalam proyek solo Jin BTS, Abyss dan The Astronaut. Perbedaan makna dan emosi yang diperoleh melalui analisis ini adalah denotasi, konotasi, dan mitos. Penelitian ini menggunakan metode kualitatif dengan pendekatan interpretatif dengan menggunakan teori semiologi Barthes (1964). Hasil penelitian menunjukkan bahwa terdapat dua perbedaan emosional yang disampaikan oleh kedua lagu dalam proyek solo Jin BTS. Lagu Abyss menceritakan pengalaman Jin ketika ia merasa terbebani dalam proses mengetahui dan mempelajari persona lain dalam dirinya. The Astronaut, di sisi lain, adalah lagu tentang bagaimana para penggemarnya memberinya harapan dan membantunya keluar dari zona di mana ia merasa kelelahan. Perbedaan emosional yang disampaikan kedua lagu tersebut adalah Burden di lagu Abyss dan Hope di lagu The Astronaut. Kata kunci: semiotika; perbedaan emosi; lirik lagu; Kim Seok-Jin